Biliary lipid composition in idiopathic bile acid malabsorption. Issue 6 (1st December 1998) - Fracchia, M; Pellegrino, S; Secreto, P; Pera, A; Galatola, G
Abstract : Background —Chronic diarrhoea is the clinical hallmark of patients presenting with idiopathic bile acid malabsorption. Its pathogenesis is unknown; colonic water secretion can be induced by dihydroxy bile acids, but it is not known whether enrichment of the bile acid pool with these bile acids occurs in such patients. Furthermore, bile acid malabsorption is known to affect biliary lipid composition, but no information is available for the idiopathic type. Aims —To verify: ( a ) whether diarrhoea in patients with idiopathic bile acid malabsorption is associated with enrichment of the bile acid pool with dihydroxy bile acids; and ( b ) whether supersaturation with cholesterol of duodenal bile occurs in such patients as a result of chronic bile acid depletion. Patients —Thirteen patients with idiopathic bile acid malabsorption diagnosed according to abnormal 75 SeHCAT test and absence of other organic diseases, and 23 control subjects. Methods —Bile rich duodenal fluid was collected during intravenous ceruletide infusion in the fasting state. Biliary lipids were analysed by enzymatic assays and bile acids by high performance liquid chromatography. Results —Patients with idiopathic bile acid malabsorption had a cholesterol saturation index similar to controls. Bile acid composition showed only a decrease in percentage cholic acid (29 (2)% versus 36 (2)%; p<0.05); the dihydroxy:trihydroxy bile acid ratio was similar to controls. Conclusions —Patients with idiopathic bile acid malabsorption do not have an increased risk of forming cholesterol gallstones. The mechanism of diarrhoea does not seem to depend on an enrichment of the bile acid pool with dihydroxy bile acids.